Out-of-pocket health spending among Medicare beneficiaries: Which chronic diseases are most costly? - Fong, Joelle H. (PLOS ONE, 2019)
Background Little is known about the impact of different types of chronic diseases on older adults’ out-of-pocket healthcare spending and whether certain diseases trigger higher spending needs than others. Methods We use data from the 2014 Health and Retirement Study representing a weighted population of 35,939,270 Medicare beneficiaries aged 65+. Generalized linear models are applied to estimate the effect of different chronic diseases on total out-of-pocket expenditure, adjusted for demographics, socio-economic status, physical health, and other factors. We also decompose total spending by expenditure categories (inpatient, non-inpatient, and prescription drug spending). Sensitivity analysis is performed using a younger sample of older adults aged 50–64. Results Cardiovascular disease, diabetes, hypertension and cancer, induce significantly higher adjusted out-of-pocket spending among older adults than other conditions. These results hold regardless how the spending differences are assessed (absolute or percentage terms). For Medicare beneficiaries, cardiovascular disease is associated with an excess out-of-pocket spending of $317 per year, followed by diabetes ($237), hypertension ($150), and cancer ($144). Prescription drug spending is singularly the most important driver of additional expenses for cardiovascular disease, diabetes and hypertension, while non-inpatient services spending accounts for the bulk of increased spending among those with cancer. Conclusions Our finding that major noncommunicable diseases impact individuals’ out-of-pocket medical spending differentially–and that service drivers of increased spending may be heterogeneous across disease types–suggest that health professionals and policymakers should recognize that certain chronic diseases exert greater financial toll on the elderly. Interventions to promote more cost efficient healthcare services and consumer choices can help older adults better cope with these expensive long-lasting conditions and reduce the overall burden of noncommunicable diseases.